Relationship between resilience and coping strategies towards stress among postgraduate counsellor trainees in pandemic COVID-19 era - Che Amat, Muhammad Asyraf; Sulong Affandi, Atirah Amalina; Farina, Nor (Macrothink Institute, 2022)
The pandemic Covid-19 has caused a lot of people to be under stress. People’s lives have been changing 360 degrees since they must adjust to the new norm that changes their everyday life. This change has also affected university students greatly and counsellor trainees are not exceptional. Counsellor trainees are expected to be able to adapt quickly despite the fast-changing situation around them. Therefore, the purpose of this study is to explore the relationship between resilience and coping strategies towards stress among counsellor trainees in Universiti Putra Malaysia. Resilience and coping strategies are the two important aspects that often been related to stress as they influence counsellor trainees’ capability in handling stress. This research is quantitative using the descriptive correlation approach, involving 32 postgraduate counsellor trainees. Descriptive statistics were conducted to identify the level of resilience, types of coping strategies and level of stress. The findings showed that postgraduate counsellor trainees have high level of resilience. Besides that, majority of them uses more emotion-focused coping strategy. It was also reported that their level of stress is moderate. The outcome of this study may help counsellor trainees to better understand themselves and become more aware of their resilience and coping strategies in stressful situations. In conclusion, the findings of the study provide practical contributions to the field of guidance and counselling.